Acoustic Outcomes Comparison Injection Versus Medialization Laryngoplasty - Sodnompil, Nergui; Palamdorj, Ganchimeg; Zestbaljir, Mendsaikhan; Orgoi, Sergelen; Tserendulam, Munkhtuya; Lkhuvsandagva, Byambasuren (Central Asian Journal of Medical Sciences, 2020)
Objectives: To determine whether injection laryngoplasty or medialization thyroplasty is more effective in the treatment of unilateral vocal fold paralysis. Methods: A prospective study of 75 patients with unilateral vocal cord paralysis who underwent autologous fat injection laryngoplasty or medialization laryngoplasty at the First Central Hospital of Mongolia between 15th Nov 2016 and 15th Jan 2020. The data analyzed included patient characteristics and type of intervention, along with the before treatment, 1 and 6 months after treatment voice parameters of electrogIottography and patients' subjective voice assessment. Results: Seventy-five patients were evaluated. The average time from intervention to post-treatment evaluation was 1 and 6 months. Improvements were demonstrated in all voice parameters (Maximum Foniation Time, Jitter, Shimmer, and Harmonic Noise Ratio) in both the injection and the medialization groups. Conclusions: In this study, objective and subjective voice analysis confirmed that injection and medialization laryngoplasty were effective in unilateral vocal cord paralysis. Both of these methods can be used to treat unilateral vocal cord paralysis.